Herpesvirus Respiratory Infections in Immunocompromised Patients: Epidemiology, Management, and Outcomes - Reid, Gail E.; Lynch, Joseph P., III; Weigt, Samuel; Sayah, David; Belperio, John A.; Grim, Shellee A.; Clark, Nina M. (Seminars in Respiratory and Critical Care Medicine, 2016)
Among immunocompromised individuals, members of the human Herpesviridae family are frequently encountered pathogens. Cytomegalovirus, herpes simplex virus 1 and 2, varicella zoster virus, Epstein–Barr virus, and human herpesvirus-6, -7, and -8 all establish latency after infection and can reactivate during periods of immunosuppression, leading to both direct and indirect adverse effects on the host including severe organ dysfunction as well as allograft rejection and loss after transplantation. While not all herpesviruses are primary respiratory pathogens, many of their manifestations include involvement of the respiratory tract. This article discusses the individual viruses, their epidemiology, and clinical manifestations as well as recommended treatment and preventive strategies.
Keywords: herpesviruses; transplantation; immunodeficiency; viral infection